Bedrock displacements in Greenland manifest ice mass variations, climate cycles and climate change - Bevis, M.; Wahr, J.; Khan, S. A.; Madsen, F. B.; Brown, A.; Willis, Michael J.; Kendrick, E.; Knudsen, P.; Box, J. E.; Van Dam, T.; Caccamise, D. J.; Johns, B.; et al. (Proceedings of the National Academy of Sciences, 2012)
The Greenland GPS Network (GNET) uses the Global Positioning System (GPS) to measure the displacement of bedrock exposed near the margins of the Greenland ice sheet. The entire network is uplifting in response to past and present-day changes in ice mass. Crustal displacement is largely accounted for by an annual oscillation superimposed on a sustained trend. The oscillation is driven by earth's elastic response to seasonal variations in ice mass and air mass (i.e., atmospheric pressure). Observed vertical velocities are higher and often much higher than predicted rates of postglacial rebound (PGR), implying that uplift is usually dominated by the solid earth's instantaneous elastic response to contemporary losses in ice mass rather than PGR. Superimposed on longer-term trends, an anomalous 'pulse' of uplift accumulated at many GNET stations during an approximate six-month period in 2010. This anomalous uplift is spatially correlated with the 2010 melting day anomaly. Published version